System Dynamics Modeling of Multi-Channel Supply Chain System: A Hypothetical LPG Distribution with Disloyal Household Customers - Petrus Setya Murdapa; Putu Dana Karningsih; I Nyoman Pujawan (Program Studi Sistem Informasi Universitas Atma Jaya Yogyakarta, 2022)
The availability of LPG in the community is a sensitive issue. If there is a shortage, it has the potential to cause chaos and inflation. The final consumers, namely households and micro business stalls, will generally be disloyal. They are not tied to one particular store to get the LPG they need. Since the number of tanks in circulation will remain constant, the analysis of LPG availability can be focused on the number of tanks. Continuous simulation method with system dynamics is generally used in system growth analysis. In this paper the method is utilized to model the discrete movement of tanks circulating in the community which in this case is represented in a much smaller system, consisting of filling stations, agents, and stores. The modeling results provide a sufficient picture of how the availability of the tank can be optimized appropriately.